2019
DOI: 10.1039/c9gc00448c
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised tetrahydrofuran fragments from carbohydrates or sugar beet pulp biomass

Abstract: Carbohydrate biomass represents a potentially valuable sustainable source of raw materials for chemical synthesis, but for many applications, selective deoxygenation/dehydration of the sugars present is necessary to access compounds with useful chemical and physical properties. Selective dehydration of pentose sugars to give tetrahydrofurans can be achieved by treatment of the corresponding N,N-dimethylhydrazones under acidic or basic conditions, with the two approaches showing complementary stereoselectivity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…41 The same reactivity was also observed with TMS-1MeO-mannose to initially provide the first example of an anhydro-C-mannoside (10), which in turn could be converted to α-allyl-rhamnopyranoside 11 (74%, Scheme 5B) in a 1-pot operation. 42 Since one of the compounds identified in the unselective silylium control experiment in Scheme 4A (top) was a C-allylfuranoside, and there are few methods for C-furanoside synthesis, 43,44 we sought to optimize our protocol for these structures. This was achieved by drawing on a recent report demonstrating that B(C 6 F 5 ) 3 could catalyze the condensative cyclization of per-silylated hexopyranoses to 1,6-anhydrosugars (i.e., 12 and a mixture of 19 and 20 in Scheme 6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…41 The same reactivity was also observed with TMS-1MeO-mannose to initially provide the first example of an anhydro-C-mannoside (10), which in turn could be converted to α-allyl-rhamnopyranoside 11 (74%, Scheme 5B) in a 1-pot operation. 42 Since one of the compounds identified in the unselective silylium control experiment in Scheme 4A (top) was a C-allylfuranoside, and there are few methods for C-furanoside synthesis, 43,44 we sought to optimize our protocol for these structures. This was achieved by drawing on a recent report demonstrating that B(C 6 F 5 ) 3 could catalyze the condensative cyclization of per-silylated hexopyranoses to 1,6-anhydrosugars (i.e., 12 and a mixture of 19 and 20 in Scheme 6).…”
mentioning
confidence: 99%
“…Since one of the compounds identified in the unselective silylium control experiment in Scheme A (top) was a C -allyl-furanoside, and there are few methods for C -furanoside synthesis, , we sought to optimize our protocol for these structures. This was achieved by drawing on a recent report demonstrating that B­(C 6 F 5 ) 3 could catalyze the condensative cyclization of per-silylated hexopyranoses to 1,6-anhydro-sugars (i.e., 12 and a mixture of 19 and 20 in Scheme ).…”
mentioning
confidence: 99%
“…Using L-arabinose, which is available from waste sugar-beet pulp, 15,16 as a test substrate, the corresponding ethyl-and phenyl thioacetals were prepared via reported procedures. 17,18 Treatment of the ethyl thioacetal with K2CO3/dimethyl carbonate (DMC) led to the formation of a complex mixture of products.…”
Section: Resultsmentioning
confidence: 99%
“…syn-4 and anti-4) under very mild conditions. 14,15 These reactions are readily scalable and provided access to useful chiral building blocks in only a few steps. Importantly, it was also observed that cyclisation of the sugar hydrazones under acidic or basic conditions provided complementary stereoselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Using l -arabinose, which is available from waste sugar beet pulp, 15 , 16 as a test substrate, the corresponding ethyl and phenyl thioacetals were prepared via the reported procedures. 17 , 18 Treatment of the ethyl thioacetal with K 2 CO 3 /dimethyl carbonate (DMC) led to the formation of a complex mixture of products.…”
mentioning
confidence: 99%